Cost of diabetes care in out-patient clinics of Karachi, Pakistan - Khuwaja Ali K; Khowaja Liaquat A; Cosgrove Peter (BMC, 2007)
Abstract Background Diabetes Mellitus (DM) is a growing epidemic and the cost of treating diabetes is largely increasing. The objective of this study was to estimate the cost-of-illness of DM among attendees of out-patient clinics in Karachi, Pakistan. This is the first study conducted from a societal perspective to estimate the cost of managing diabetes in Pakistan. Methods A prevalence-based 'Cost-of-Illness' study for diabetes care was conducted in six different out-patient clinics of Karachi, Pakistan from July to September 2006. A pre-tested questionnaire was administered to collect the data from 345 randomly selected persons with diabetes. Results The annual mean direct cost for each person with diabetes was estimated to be Pakistani rupees 11,580 (US$ 197). Medicines accounted for the largest share of direct cost (46%), followed by laboratory investigations (32%). We found that increased age, the number of complications and longer duration of the disease significantly increase the burden of cost on society (p < 0.001). Comparing cost with family income it was found that the poorest segment of society is spending 18% of total family income on diabetes care. Conclusion This study concluded that substantial expenditure is incurred by people with diabetes; with the implication that resources could be saved by prevention, earlier detection and a reduction in diabetes co-morbidities and complications through improved diabetes care. Large scale and cost-effective prevention programs need to be initiated to maximise health gains and to reverse the advance of this epidemic.